Core Competencies of an Anti-racist Physician: Elective Course for Undergraduate Medical Students - J. Corey Williams; Zharia Crisp; Brendan Crow; Aaron Alexander-Bloch; Katie Galvin; Zheala Qayyum; Jaya Aysola; Susan M. Cheng (Association of American Medical Colleges, 2024)
Introduction Medical schools seeking to correct and reform curricula towards anti-racist perspectives need to address anti-Black forms of racism specifically and teach students critical upstander skills to interrupt manifestations of racism. We developed a course to teach preclinical medical students basic anti-racism competencies including recognition and awareness of anti-Black racism in medicine and upstander skills to advocate for patients and colleagues. Methods In 2021 and 2022, we designed, implemented, and evaluated an elective course for second-year medical students (N = 149) to introduce competencies of anti-racism focusing on upstander skills for addressing anti-Blackness. We designed three patient cases and one student-centered case to illustrate manifestations of anti-Black racism in medicine and used these cases to stimulate small-group discussions and guide students toward recognizing and understanding ways of responding to racism. We designed pre- and postassessments to evaluate the effectiveness of the course and utilized anonymous feedback surveys. Results Participants showed significant improvement in pre- to postassessment scores in both years of the course. The anonymous feedback survey showed that 97% of students rated the course at least somewhat effective, and the qualitative responses revealed five core themes: course timing, case complexity, learner differentiation, direct instruction, and access to resources. Discussion This course reinforces upstander competencies necessary for advancing anti-racism in medicine. It addresses a gap in medical education by reckoning with the entrenched nature of anti-Black racism in the culture of medicine and seeks to empower undergraduate medical students to advocate for Black-identifying patients and colleagues.